2022
DOI: 10.1155/2022/4887259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Gegen Qinlian Decoction for Pediatric Diarrhea: A Systematic Review and Meta-Analysis

Abstract: Objective. To evaluate the clinical efficacy and safety of Gegen Qinlian decoction in the treatment of pediatric diarrhea. Methods. A search for relevant RCTs was performed from which a systematic review and meta-analysis was conducted. This meta-analysis was registered at INPLASY (reference number ID: INPLASY202180105). Results. (1) Eleven trials involving 1126 patients were included in the meta-analysis. (2) Two trials recorded the adverse events. (3) The meta-analysis showed that compared with the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…More significantly, J Jiawei GQD improved colonic inflammation in UC rat models in both the general environment and the Lingnan region by increasing the production of propionate and total short-chain fatty acids (SCFAs) in colitis rats, regulating medium and long-chain fatty acids (M-LCFAs), bile acids (BAs) homeostasis, and amino acids (AAs) metabolism [185]. After a systematic review and meta-analysis, they concluded that GQD was significantly effective in pediatric diarrhea and recommended that it should be applied for a period of greater than five days along with unaltered compounded formulas [186].…”
Section: Gegen-qinlian Decoction (Gqd)mentioning
confidence: 99%
“…More significantly, J Jiawei GQD improved colonic inflammation in UC rat models in both the general environment and the Lingnan region by increasing the production of propionate and total short-chain fatty acids (SCFAs) in colitis rats, regulating medium and long-chain fatty acids (M-LCFAs), bile acids (BAs) homeostasis, and amino acids (AAs) metabolism [185]. After a systematic review and meta-analysis, they concluded that GQD was significantly effective in pediatric diarrhea and recommended that it should be applied for a period of greater than five days along with unaltered compounded formulas [186].…”
Section: Gegen-qinlian Decoction (Gqd)mentioning
confidence: 99%